Antimicrobial peptide human β-defensin-2 improves in vitro cellular viability and reduces pro-inflammatory effects induced by enteroinvasive Escherichia coli in Caco-2 cells by inhibiting invasion and virulence factors’ expression - Fusco, Alessandra; Savio, Vittoria; Perfetto, Brunella; Mattina, Roberto; Donnarumma, Giovanna (Frontiers in Cellular and Infection Microbiology, 2022)
Escherichia coli is one of the commensal species most represented in the intestinal microbiota. However, there are some strains that can acquire new virulence factors that enable them to adapt to new intestinal niches. These include enteroinvasive E. coli (EIEC) that is responsible for the bacillary dysentery that causes severe diarrheal symptoms in both children and adults. Due to the increasing onset of antibiotic resistance phenomena, scientific research is focused on the study of other therapeutic approaches for the treatment of bacterial infections. A promising alternative could be represented by antimicrobial peptides (AMPs), that have received widespread attention due to their broad antimicrobial spectrum and low incidence of bacterial resistance. AMPs modulate the immune defenses of the host and regulate the composition of microbiota and the renewal of the intestinal epithelium. With the aim to investigate an alternative therapeutic approach, especially in the case of antibiotic resistance, in this work we created a line of intestinal epithelial cells able to express high concentrations of AMP human β-defensin-2 (HBD-2) in order to test its ability to interfere with the pathogenicity mechanisms of EIEC. The results showed that HBD-2 is able to significantly reduce the expression of the proinflammatory cytokines by intestinal epithelial cells, the invasiveness ability of EIEC and the expression of invasion-associated genes.